Stock Liquidity and Dividend Policy - Nadia Sawitri, A; Sulistyowati, C (KnE Social Sciences, 2018)
This research aims to determine the effect of stock liquidity on dividend policy. This research is conducted on nonfinancial firms listed on the Indonesia Stock Exchange over the period of 2014–2016, using purposive sampling method. This research uses two proxies of stock liquidity – Amihud illiquidity ratio and share turnover. This research uses multiple linear regression in order to determine the effect of the independent variable, which is stock liquidity, and control variables consisting of firm size, profitability, leverage, and cash holding on dividend policy as the dependent variable. The analysis shows that stock liquidity as proxied by Amihud illiquidity ratio has a negative insignificant effect, stock liquidity as proxied by share turnover has a negative significant effect, firm size, profitability, leverage and cash holding have a positive and significant effect, while leverage has a negative but insignificant effect on dividend policy. Thus, it can be concluded that stock liquidity has an effect on dividend policy in nonfinancial public firms in Indonesia. Keywords: stock liquidity, Amihud illiquidity ratio, share turnover, dividend policy